2018
DOI: 10.2147/ibpc.s130277
|View full text |Cite
|
Sign up to set email alerts
|

Morning blood pressure surge: pathophysiology, clinical relevance and therapeutic aspects

Abstract: Morning hours are the period of the day characterized by the highest incidence of major cardiovascular events including myocardial infarction, sudden death or stroke. They are also characterized by important neurohormonal changes, in particular, the activation of sympathetic nervous system which usually leads to a rapid increase in blood pressure (BP), known as morning blood pressure surge (MBPS). It was hypothesized that excessive MBPS may be causally involved in the pathogenesis of cardiovascular events occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
55
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 79 publications
(97 reference statements)
0
55
0
3
Order By: Relevance
“…2 However, the strength of the association between the MS and cardiovascular events is largely dependent on the definition and threshold used to define the MS and of the patients' characteristics, with one study also reporting a significant association for a blunted MS. 3 Few studies have also reported substantial ethnic differences in the degree of MS, a finding which can help understand the role of ethnic factors in cardiovascular risk assessment and identify the most effective measures to be implemented for preventing BP-related cardiovascular events (Table 1). [9][10][11] Although the major strength of the study by Gavin et al stands in the rigorous methodology employed to assess the MS, nonetheless the study is not free of some critical issues. One longitudinal study, based on mixed populations from Europe, Asia, and South America, anticipated some potential differences in the risk of cardiovascular events according to the ethnic group.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…2 However, the strength of the association between the MS and cardiovascular events is largely dependent on the definition and threshold used to define the MS and of the patients' characteristics, with one study also reporting a significant association for a blunted MS. 3 Few studies have also reported substantial ethnic differences in the degree of MS, a finding which can help understand the role of ethnic factors in cardiovascular risk assessment and identify the most effective measures to be implemented for preventing BP-related cardiovascular events (Table 1). [9][10][11] Although the major strength of the study by Gavin et al stands in the rigorous methodology employed to assess the MS, nonetheless the study is not free of some critical issues. One longitudinal study, based on mixed populations from Europe, Asia, and South America, anticipated some potential differences in the risk of cardiovascular events according to the ethnic group.…”
mentioning
confidence: 99%
“…8 This methodology relies upon a line of best fit based on the entire recording and can independently estimate the power of the MS and the rate of the morning rise during the transition period, making no assumption about when the BP is rising. [9][10][11] Although the major strength of the study by Gavin (Table 1). [9][10][11] Although the major strength of the study by Gavin (Table 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although statistically significant between-groups differences in indices of BP morning surge were not obtained by a majority of comparisons, the fact of an increase in magnitude and velocity of BP morning surge in CKD children with reduced renal function deserves attention. It should be noted that the morning BP surge is mediated by rapid sympathetic nervous system activation with the development of vasoconstriction [7,22]. Also, in the morning, the endothelial function decreases, and the level of thrombogenic factors increases [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that high BP plays the role of an independent risk factor for rapid reduction in glomerular filtration rate (GFR) in patients with renal diseases [6][7][8][9]. BP monitoring is important for the management of patients with CKD, both for the conventional cardiovascular risk reduction and long-term preservation of kidney function [8].…”
Section: Introductionmentioning
confidence: 99%